The state and prospects of the development of small and medium business in the conditions of war in Ukraine - Viktoriia M. Orlova; Olena R. Serhieieva; Oksana V. Kuzmenko (Êvropejsʹkij Vektor Ekonomìčnogo Rozvitku)
This paper investigates the current state of small and medium business in Ukraine. The protracted nature of the war in Ukraine significantly destabilizes the activities of the subjects of this sector and leads to the deterioration of its development indicators. In particular, a decrease in quantity of active entities small and medium business, a decrease in the rate of registration of new entities, a shortage of own working capital in most small and medium enterprises will have a negative impact on the national economy. The main obstacles to the recovery and development of business activity during the period of validity of state of war are identified. It is the lack of financial resources; continuation of hostilities; interruptions in electricity, water and heat supply; destruction of logistics; increase in production costs; insufficient quantity of paying customers. The peculiarities of state support of small and medium business in Ukraine during the war are considered. The problems hindering the development of national small and medium business in the conditions of war are identified. It is the absence of a program document on the development of the small and medium business sector; low level of access to finance by small and medium business entities; insufficiently developed state financial support programs for IT startups; inefficiency of industrial parks. Proved, that the prospects of the development of small and medium business largely depend on ensuring the implementation of an effective state policy to stimulate its development. In this context, the priorities of the state policy in the sphere of stimulating the development of small and medium business in the conditions of the war in Ukraine are substantiated. It is the development of the State program for promoting the development of small and medium business in Ukraine, coordination of strategies and programs for the development of small and medium business at the state, regional and local levels; attraction of money from international financial organizations and international donors; creation of conditions for increasing the level of access of small and medium enterprises to finance; expansion of state grant support for IT startups; implementation of mechanisms of tax benefits for entities that resume their activities in the de-occupied territories; expansion and creation of new industrial parks with developed engineering and transport infrastructure, creation of favorable conditions for the development of small and medium business within the industrial park.